1994
DOI: 10.4141/cjps94-086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an oat companion crop on irrigated alfalfa yield and economic returns in southwestern Saskatchewan

Abstract: However, their use has been common with inigated alfalfa to control weeds and produce economic yields in the establishment year. The objective of this study was to determine the effect of an oat companion crop 9n forage. yield and economic returns ior irrigated afafu. In four irrigated trials at Swift Current, Saskatchewan, alfalfa was planted with and without a companion oat (Avina sativa L.) crop. The d-irect-seeded alfalfa produced harvestable yields in three of four trials, with forage yields ranglng from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…The NPV for NH was significantly higher than for HB. Jefferson and Zentner (1994) found similar results for alfalfa establishment using oat grain and forage companion crops under irrigation. Returns were found to be generally higher when the oat companion crop was harvested for hay, but this depended upon the price of oat hay, oat grain and alfalfa hay.…”
Section: Overall Net Present Valuesupporting
confidence: 63%
See 2 more Smart Citations
“…The NPV for NH was significantly higher than for HB. Jefferson and Zentner (1994) found similar results for alfalfa establishment using oat grain and forage companion crops under irrigation. Returns were found to be generally higher when the oat companion crop was harvested for hay, but this depended upon the price of oat hay, oat grain and alfalfa hay.…”
Section: Overall Net Present Valuesupporting
confidence: 63%
“…There was an economic benefit under irrigation to include a companion crop in both the short and long term. Jefferson and Zentner (1994) found that higher forage yields after establishment when no companion crop was included would have to persist for at least 2 yr to be more profitable than establishment with a companion crop. Moyer et al (1995) found that firstyear yields after establishment with a companion grain crop on irrigation at Lethbridge, Alberta were reduced by about 33%, but subsequent cuttings were not affected.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The use of companion crops at Nipawin increased the 2-yr net returns by $72 ha -1 at the low forage price and by $19 ha -1 at the medium forage price, but at the high forage price their use reduced average net returns by $33 ha -1 . By comparison, under conditions when water is non-limiting, Jefferson and Zentner (1994) reported that economic returns in the establishment year were highest when alfalfa was grown with an oat (Avena sativa L.) companion crop that was harvested for hay, but when evaluated over a 3-yr period, they found little difference among direct-seeded and the companion crop methods Table 10. Two-year production costs and net returns for companion crops by soil zone in Saskatchewan ness to survive more than one Saskatchewan winter and the resulting yield of Nitro alfalfa-grass mixtures was generally similar to grass monoculture.…”
Section: Economic Returnsmentioning
confidence: 99%
“…Understanding the mechanisms of plant tolerance to drought stress and developing high-yielding plant cultivars for drought conditions are critical research topics (Painawadee et al, 2009). Jefferson et al (1994) reported that sainfoin-alfalfa (Medicago sativa L.) mixtures are not sustainable in semiarid environments because the seed mixture was dominated by alfalfa within 2 yr after seeding due to water stress. Jefferson et al (1994) reported that sainfoin-alfalfa (Medicago sativa L.) mixtures are not sustainable in semiarid environments because the seed mixture was dominated by alfalfa within 2 yr after seeding due to water stress.…”
mentioning
confidence: 99%